Peran Zat Gizi dan Senyawa Bioaktif Daun Kelor (Moringa oleifera) dalam Pengendalian Diabetes Melitus: Literature Review - Ainul Mardiah; Syahrial Syahrial; Jeallyza Muthia Azra (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Diabetes mellitus is a metabolic disease that requires effective blood glucose control. Moringa oleifera leaves contain various nutrients and bioactive compounds that have potential benefits in diabetes management.This literature review aimed to examine the role of nutrients and bioactive compounds in Moringa oleifera leaves for diabetes mellitus management based on studies published between 2021 and 2026. A literature review was conducted by searching articles from Google Scholar, PubMed, ScienceDirect, and SpringerLink databases. A total of 10 articles that met the inclusion criteria were analyzed. Moringa oleifera leaves were found to reduce blood glucose levels, improve insulin sensitivity, enhance lipid profiles, and decrease oxidative stress. These effects are attributed to the presence of flavonoids, polyphenols, quercetin, chlorogenic acid, dietary fiber, vitamin C, and β-carotene, which contribute to glucose metabolism regulation through various biological mechanisms. Moringa oleifera leaves have strong potential as a functional food for diabetes mellitus management due to their nutrient and bioactive compound content, which supports blood glucose regulation. Keywords: Moringa Oleifera, Diabetes Mellitus, Functional Food, Bioactive Compounds. ABSTRAK Diabetes melitus merupakan penyakit metabolik yang memerlukan pengendalian kadar glukosa darah. Daun kelor (Moringa oleifera) mengandung berbagai zat gizi dan senyawa bioaktif yang berpotensi membantu pengelolaan diabetes. Mengkaji peran zat gizi dan senyawa bioaktif daun kelor dalam pengendalian diabetes melitus berdasarkan penelitian tahun 2021–2026.Literatur review dilakukan melalui pencarian artikel pada Google Scholar, PubMed, ScienceDirect, dan SpringerLink. Sebanyak 10 artikel yang memenuhi kriteria inklusi dianalisis. Daun kelor terbukti mampu menurunkan kadar glukosa darah, meningkatkan sensitivitas insulin, memperbaiki profil lipid, dan mengurangi stres oksidatif. Efek tersebut dipengaruhi oleh kandungan flavonoid, polifenol, quercetin, asam klorogenat, serat pangan, vitamin C, dan β-karoten yang bekerja melalui berbagai mekanisme pengendalian metabolisme glukosa. Daun kelor berpotensi sebagai pangan fungsional dalam pengelolaan diabetes melitus karena kandungan zat gizi dan senyawa bioaktifnya yang mendukung pengendalian glukosa darah. Kata Kunci: Moringa Oleifera, Diabetes Melitus, Pangan Fungsional, Senyawa Bioaktif.